KREATIVITAS GURU PAUD DALAM MEMANFAATKAN BAHAN SISA DAN BAHAN ALAM SEBAGAI SUMBER BELAJAR DIKECAMATAN KEMPAS KABUPATENINDRAGIRI HILIR - Ratnasari, Ucik; Indarto, Wusono; Risma, Devi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract:This research is motivated due to a phenomenon in which the teacher. Most of the teachers have not been able to make the idea to create Educational Games, by it self the lack of understanding of the Educational Game Equipment in accordance with the needs of children, some teachers are less skilled and less patient in processing residue and natural ingredients into Educational Game Equipment, low the willingness of teachers to process waste materials and natural materials into tools Educational Games, teachers lack confidence in their own works made which resulted in the teachers tend to use methods and tools watch games, such as children's worksheets. The purpose of this studywas to determin ethe creativity of early childhood teachers in District Kempas Indragiri Hilir. The populationin this study were 40 teachers and the sample used is saturated samples. Measuring instruments used in this study was a questionnaire. The technique of analysis in this research is by using techniques percentage. The results were obtained by an average of 92,4%. Where the value of 92,4 is at the value of 86,6 to 95,4 or the medium category and the percentage of each the 5 indicators are 4 indicator were high and were medium.Keywords: Creativity Of Teachers, Learning Resources